The Indonesia Stock Exchange Companies: The Existence of Institutional Ownership as a Moderating Variable of the Influence of Financial Ratio on Financial Distress - Refiana Dwi Maghfiroh; Ulil Hartono; Nadia Asandimitra Haryono (Journal of Business and Management Review, 2022)
Financial distress is a condition that occurs before a company goes bankrupt and can be experienced by companies that are under pressure due to the impact of the COVID-19 pandemic. The purpose of this research is to determine the existence of institutional ownership as a moderating of the influence of financial ratio on financial distress in infrastructure, trading, service, and investment companies listed on the Indonesia Stock Exchange for the period 2020-2021 through logistic regression and moderated regression analysis. This type of research is quantitative by using a sample of 125 companies determined through a purposive sampling technique. The results showed that the profitability and liquidity ratio had a significant and negative impact on financial distress. While institutional ownership is not able to moderate the effect of profitability and liquidity of the firms toward better financial distress, because institutional ownership is centralized and owned by foreigners. This causes management control to be not optimal so that the decisions taken by management are not always in line with the interests of shareholders. Implications in this study are considering the profitability and liquidity ratio in predicting financial distress that can be used by companies, potential investors, and future researchers.